Techno-economic Feasibility of Renewable Energy Based Stand-alone Energy System for a Green House: Case Study. Issue 1 (25th May 2018) - Khalid, Farrukh; El-Emam, Rami S.; Hogerwaard, Janette; Dincer, Ibrahim
As the negative impacts of fossil fuel consumption for power generation become increasingly globally evident—particularly the effects of greenhouse gas (GHG) emissions on climate change—so too does the conversely positive potential of renewable energies to reduce the rate of damaging environmental impacts as energy demand grows. In addition to the clear environmental advantage, stand-alone renewable energy power generation options offer energy security and stability in regions where socio-political issues or geographic location might otherwise pose access limitations on fuel and/or electric grid power, particularly in remote communities. This paper discusses the techno-economic considerations for renewable energy power systems in residential community applications. A case study for a residential house in New Cairo in Egypt compares two different renewable energy systems that meet typical electrical demand for this region. Economic assessment—in terms of system net present cost (NPC) and levelized cost of electricity (LCOE)—provide measures for system performance comparison and optimization. The LCOE for system-I and system-II are found to be 0.359/kWh and 0.373/kWh, respectively.